Exploring the psychosocial risk and resilience among the lesbian community in Selangor, Malaysia - Karim, Nursyahira; Marof, Aini Azeqa; Kamarudin, Mohd Shahrul (Human Resource Management Academic Research Society (HRMARS), 2023)
This study narrows its focus to rigorously investigate the distinct themes that either attract or repel lesbians in Selangor, Malaysia, from participating in same-sex sexual activities. Conducted within the framework of qualitative research, the study utilizes a phenomenological methodology to delve into the emotional and psychological complexities that contribute to these behaviors. The study population consists of five lesbian individuals, who were identified through a snowball sampling technique. Data was collected through a combination of online and face-to-face semi-structured interviews, aiming to allow participants to express themselves freely and comprehensively. For data analysis, a thematic approach was employed to interpret the nuanced motivations and deterrents identified by the study participants. The study successfully isolated several significant factors of attraction. Notably, familial influence, compatibility with partners, negative experiences with men, identity confusion, engagement with social media, and strong social support networks were found to be key motivators for lesbians to engage in same-sex sexual activities. Conversely, the research also identified two main themes that serve as deterrents. These were rooted in concerns about family acceptance and a deep-seated desire for a more traditional family structure. By isolating these key factors, the study aims to offer a focused, nuanced understanding of what encourages or deters sexual activity within the lesbian community in Selangor, Malaysia. This focused examination can serve as a crucial resource for social scientists, policymakers, and LGBTQ+ advocacy groups looking to understand the unique challenges and motivators within this specific demographic.